2019
DOI: 10.36089/nu.v1i2.62
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Peran Orang Tua Dalam Anticipatory Guidance Sibling Rivalry Dan Kecerdasan Emosional Dengan Kejadian Sibling Rivalry Pada Anak Usia Prasekolah

Abstract: Sibling rivalry is the natural jealousy or dislike feeling of a children to a new child in the family. Preliminary study result obtained 6 (60%) children have sibling rivalry. The purpose of the study was to analyze the relationship of parent role in anticipatory guidance sibling rivalry and emotional intelligence with sibling rivalry incident in preschooler. The design of this research is correlational analytic with cross sectional approach. The independent variable is the parent role in the anticipator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The results showed that the role of parents in anticipatory guidance sibling rivalry was lacking, most of the children experienced severe sibling rivalry, 13 children with a percentage of 56.5%, the role of parents in anticipatory guidance was sufficient with moderate sibling rivalry as many as 7 respondents with a percentage of 50%. 14 Children who experience sibling rivalry can show anger, sadness, and fear. The older child will feel that his mother loves his younger brother more, so the child shows anger and hates anything about the younger sibling.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the role of parents in anticipatory guidance sibling rivalry was lacking, most of the children experienced severe sibling rivalry, 13 children with a percentage of 56.5%, the role of parents in anticipatory guidance was sufficient with moderate sibling rivalry as many as 7 respondents with a percentage of 50%. 14 Children who experience sibling rivalry can show anger, sadness, and fear. The older child will feel that his mother loves his younger brother more, so the child shows anger and hates anything about the younger sibling.…”
Section: Discussionmentioning
confidence: 99%
“…Perilaku negative anak yang mengalami sibling rivalry apabila tidak segera ditangani maka akan terekam di bawah alam sadar yang dapat menjadi cikal bakal perilaku destruksif yang terbawa hingga usia dewasa. Terdapat upaya menanggulangi dampak negative perkembangan anak sibling rivalry, maka diperlukan peran orang tua untuk menangani persaingan antara saudara kandung (Noviana, 2019). Keperawatan sebagai bagian dari pelayanan kesehatan memegang peranan penting dalam upaya peningkatan kesehatan anak secara komperehensif fisik, mental, serta hubungan sosial sehingga anak memperoleh perkembangan secara optimal sesuai dengan usia tugas perkembangan yang dapat melibatkan peran orang tua (Yektiningsih et al, 2021).…”
unclassified